EKSTRAKSI MINYAK NILAM DENGAN METODE FERMENTASI MENGGUNAKAN Rhizopus oryzae (Extraction of Patchouli Oil by Fermentation Method with Rhizopus oryzae) - Busthan, Meuthia; Djafar, Fitriana (Baristand Industri Banda Aceh, 2015)
This study aims to acquire and apply new techniques patchouli oil refining the people andassess the quality of patchouli oil produced. In this study, patchouli leaf materials used were obtainedfrom farmers Aceh Jaya. Extraction using Rhizopus oryzae 1% of the weight of the material, water ratioof 1: 5. The yield of raw materials dried leaves is 3.3%. The yield of fresh leaves as raw material is 2.1%.The yield on the addition of Rhizopus oryzae is 1.5%. Quality testing is done based on the qualityrequirements of patchouli oil (SNI 06-2385-2006). Pachouli levels of alcohol in the extraction of driedleaves at 25.43%, the extraction of fresh leaves at 55.01% and extraction in addition Rhizopus oryzae at43.89%. The refractive index obtained in the extraction of dried leaves is 1.50642, 1.51071 for theextraction of fresh leaves and extraction in addition Rhizopus oryzae obtained by 1.51281. Gravity of theextraction of dried leaves obtained at 0.955, extraction of fresh leaf extract at 0.961 and in additionRhizopus oryzae at 0.966.